Trust in Cultural Institutions and Interfirm Cooperation: Evidence from Religious Scandals - Dupont, Quentin; Freeman, Kayla M. (Journal of Financial and Quantitative Analysis, 2026)
An abstract is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.